If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2(x + 7) = 10 + -3(x + -3) Reorder the terms: 6 + 2(7 + x) = 10 + -3(x + -3) 6 + (7 * 2 + x * 2) = 10 + -3(x + -3) 6 + (14 + 2x) = 10 + -3(x + -3) Combine like terms: 6 + 14 = 20 20 + 2x = 10 + -3(x + -3) Reorder the terms: 20 + 2x = 10 + -3(-3 + x) 20 + 2x = 10 + (-3 * -3 + x * -3) 20 + 2x = 10 + (9 + -3x) Combine like terms: 10 + 9 = 19 20 + 2x = 19 + -3x Solving 20 + 2x = 19 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 20 + 2x + 3x = 19 + -3x + 3x Combine like terms: 2x + 3x = 5x 20 + 5x = 19 + -3x + 3x Combine like terms: -3x + 3x = 0 20 + 5x = 19 + 0 20 + 5x = 19 Add '-20' to each side of the equation. 20 + -20 + 5x = 19 + -20 Combine like terms: 20 + -20 = 0 0 + 5x = 19 + -20 5x = 19 + -20 Combine like terms: 19 + -20 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2
| 40x^2-x+4000=0 | | 5x+11=5x-5 | | 16+8y=48 | | -1+2-(-3)=10 | | -4j=39 | | -34-5x=-12x+64 | | A+2=12 | | 4x+8+2x+3=51 | | -4(x-1)+2x=34+3x | | 7b^2+-14b+7=0 | | -3x-86=-9x+82 | | -7k-2k= | | -6-z=12 | | (4x^2+2)-(2x^2+3)= | | 11x-61=6x+89 | | X^2+4x=44 | | 4(y-4)-8y=20 | | 3(1-7n)= | | r-10=-12 | | x^2+3x=-4(-2x+1)-2 | | 12x-33=3x+75 | | -4.9x^2+9x+1.2=0 | | 2(2y-3)+3x=7 | | 0=2(2x^2-103x+546) | | 4x=x+5+2x-1 | | 4(j+5)=2 | | 13-2=j+6 | | -4(4a-8)= | | -4(4a-7)= | | Y=-12e^2x+36e^4x | | r+0.48=1.6 | | h(t)=-16x^2+85 |